Blood Management and Risk Assessment for Transfusion in Pediatric Spinal Deformity Surgery - Pedro Fernandes; Joaquim Soares do Brito; Isabel Flores; Jacinto Monteiro (Advances in Hematology)
Objectives. Evaluate the impact of a Quality and Safety Program (QSP) on the reduction of blood loss and transfusion needs in pediatric spinal deformity surgery, while defining risk factors for transfusion. Background. Multimodal plan aiming to minimize transfusion needs has been shown to reduce transfusions and index rates in spinal deformity surgery. Anticipating blood loss and transfusion may help direct resources to patient needs or encourage reconsideration of the surgical plan. Methods. This is a single-center retrospective study of prospectively collected data. Impact of this multimodal plan was studied on idiopathic deformities (Group A, 109 patients) and scoliosis associated with syndromic, neuromuscular, and muscular dystrophies (Group B, 100 patients), both before and after QSP. Results. A decrease in total estimated blood loss was observed. In Group A, transfused patients decreased from 83.7% to 28% (p<0.001, odds: 0.077), and, in Group B, from 98.7% to 66% (p<0.01, odds: 0.038). Pearson’s correlation identified patient body weight (r = 0.245, p=0.001) and Cobb angle (r = 0.175, p=0.017) as factors related to blood loss. A linear regression model to estimate hematic losses revealed that only body weight and transfusion showed predictive power, resulting in a low predictive model (R2 = 0.156; F(3,167) = 15.483, p<0.001). A mediated model to explain blood loss was built based on a set of variables influencing transfusion which is, in turn, related to blood loss. Conclusion. Transfusion needs in scoliosis surgery can be substantially reduced following a multimodal approach. The success of a program is strongly dependent on team effort, and the introduction of a risk assessment tool for transfusion needs indirectly assesses surgical risk, thus allowing relocation of resources to decrease blood loss.